Nutritional value of important commercial fish from Iraqi waters - Hantoush, A.A.; Al-Hamadany, Q.H.; Al-Hassoon, A.S.; Al-Ibadi, H.J. (Mesopotamian Journal of Marine Sciences, 2022)
Knowledge of the proximate chemical composition (protein, fat, moisture and ash) of fish species can be used to determine their nutritional value and to plan the industrial and commercial processing. Ten species of fish from marine and fresh waters of Iraq were studied. In marine and freshwater fish species, the highest level of moisture content was observed in Ilisha megaloptera (79.04 %) and Cyprinus carpio (78.51 %), and the lowest was observed in Chirocentrus dorab (73.74 %) and Liza abu (71.23 %). The lipid contents in the muscles of marine fish species ranged from 1.28 % in Ilisha megaloptera to 4.63 % in Cynoglossus bilineatus, while in freshwater fish species ranged from 3.16 % in Cyprinus carpio to 6.03 % in Liza abu. The highest protein values in the marine and freshwater fish species were recorded in Chirocentrus dorab (18.61 %) and Liza abu (19.15 %), and the lower values were in Cynoglossus bilineatus (11.77 %) and Cyprinus carpio (14.74 %). The percentage of ash content in the marine and freshwater fish species was highest in Cynoglossus bilineatus (4.24 %) and Liza abu (3.25 %), and lowest in Ilisha megaloptera (1.25 %) and Barbus xanthopterus (1.28 %). The results showed that the proximate composition of the fish varied significantly among the various fish species. The results revealed that moisture content was high when lipid was low indicating a significant inverse relationship between the two components (r = - 0.711).